-5g+4+8g=43

Simple and best practice solution for -5g+4+8g=43 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5g+4+8g=43 equation:



-5g+4+8g=43
We move all terms to the left:
-5g+4+8g-(43)=0
We add all the numbers together, and all the variables
3g-39=0
We move all terms containing g to the left, all other terms to the right
3g=39
g=39/3
g=13

See similar equations:

| 11-2n+8n=65 | | 5y-37=13 | | 8.26=q+2 | | -4+x=-3-4x | | -56=-4(v+10) | | d+3=15.83 | | -65=-4(v+10) | | -4=-17+x* | | -4x-3=-5x+2x | | 3(m-5)=-2(m-5) | | x2/4-20=-4 | | f+7=13.4 | | 2x+131+x+85=46 | | 3x+2=134 | | 96=-4v | | -x+6x=(x-7 | | .08(5x+15)=2.6-(x+3) | | 19.5=3z | | -10+n=6 | | 0.35n=9.8 | | 9x-x=4x+8 | | 1x-4=3x | | 7,2+c=19 | | 5+3x-1=3 | | P(x)=x2+1x-4 | | 8x+10=-4x-14 | | 7/4x=40 | | x-1+2x-4=5 | | (5/x)+(2/2x)-3=(5/3x) | | x-2+2x-4=7 | | 7k+6=27 | | 6g-5=19 |

Equations solver categories